PENERAPAN ALGORITMA NAÏVE BAYES UNTUK MEMPERPANJANG KONTRAK KERJA KARYAWAN PADA PT INDOSAT OOREDOO - Sabila Putri Adriatasya; Dedi Suhendro (STMIK Sinar Nusantara, 2025)
Contract employees are company resources who carry out operational activities for a certain period of time based on a contract agreement. In companies that implement a contract work system, every year there are employees who get contract extensions and those who don't. Contract extensions are usually given to employees with satisfactory performance. Determining the eligibility for employee contract extensions often faces obstacles in the form of difficulty in decision making and requires a long time and process. Therefore, this study aims to assist the decision-making process by classifying employees into “Eligible” and “Ineligible” categories based on four variables, namely age, length of service, tardiness, and achievement. This study uses data from PT. Indosat Ooredoo employees as a sample with a total of five employees consisting of two classes. Based on calculations using the Naïve Bayes Algorithm, the classification results show that three employees are in the “Eligible” class and two employees are in the “Ineligible” class. This study shows an accuracy rate of 100%.